Windfield related light-trap catches of Nephotettix spp. (N. virescens Distant and N. nigropictus stål), vectors of rice tungro virus in West Bengal - MUKHOPADHYAY, SUJATA; MUKHOPADHYAY, S. (MAUSAM, 1997)
ABSTRACT. Regular peak catches of rice green leafhoppers, Nephoteltix virescens (Distant) and N. nigropictus (Stal) are usually obtained in a light-trap 60 ± 14 days after the peak monsoon rains in August in West Bengal. In 1986, in addition to this peak catch, very high catches were obtained on two different dates, 17 September and 10 November. The high catch on 17 September was probably due to the increase of the effective trap radius caused by the overcast sky and by the presence of a resident population. The high catch on 10 November was due to the transport of the insects by cyclonic winds and deposition in a zone of light and variable winds (at a convergence) real the trapping site. Trajectory analysis indicates that these insects may have been brought from the north-east, upto about 280 km away from the trapping site.